Oddział łódzki Towarzystwa Kultury Polskiej i jego biblioteka (1908–1913) - Konieczna, Jadwiga (Acta Universitatis Lodziensis. Folia Librorum, 2014)
In this article the author presented the activities of the founded in 1908 Society of Polish Culture’s Łódź Department for organizing public scientific library in Łódź. Reading room opened in 1909 and library opened in 1910 functioned only for four years, as in 1913 Russian authorities closed down the Society of Polish Culture. Despite the short period of functioning, the library of the Society of Polish Culture played an important role in shaping the book culture in Łódź.